Man is the Measure of All Things: Marcuse and Rawls on Human Nature - Hazman M.B. Baharom (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2024)
In the development of post-war philosophy, the thought of the Frankfurt School thinkers has been seminal in pushing the boundaries of the discipline. One of these thinkers include Herbert Marcuse (1898 â€“ 1979). Consequently, in the realm of moral and political philosophy, the post-war philosophy that was plagued by the interlocking clash between the consequence-based utilitarian theories and duty-based Kantian theories has found its new ground in Rawlsian liberalism, spearheaded by John Rawls (1921 â€“ 2002). Using qualitative textual data found in the most important works of both philosophers, this paper would explore the ways in which Marcuseâ€™s ideas have influenced Rawls in his outlook on human nature. Examined through the framework of secularization outlined by Syed Muhammad Naquib al-Attas (1931 â€“), the direction of influence has also intensified the process of â€œdeconsecration of values,â€ hence characterizing a more secular worldview.